Informalidade no ambiente construído e segregação socioespacial no Platô das Guianas: o caso de Santana no Amapá e de Caiena na Guiana Francesa - Jodival Mauricio da Costa; Luana Rocha de Souza; Jacy Soares Corrêa Neto (Confins)
The understanding of the Amazon increasingly distances itself from the common sense and its generalities towards a better approximation of its cities. The State intervention and the role of large companies are deciding factors in the Amazonian urban processes, which are responsible in large part for the structuration of its cities. The objectives of this article consist in understand the urban transformations that have occurred in the cities of Cayenne, in French Guiana, and Santana in the State of Amapá (Brazil,) in a particular the socio-spatial segregation processes in the built environment, and explain the influence of public policies in the structuration of these cities. The procedures adopted are data collection in research institutions, consultations of existing urban plans and observations in loco. The results show that both urban centers lack in public policy and adequacy of cities to changes in population dynamics.